Genome and Phylogenetic Analysis of Genes Involved in the Immune System of Solea senegalensis – Potential Applications in Aquaculture - García-Angulo, Aglaya; Merlo, Manuel A.; Rodríguez, María E.; Portela-Bens, Silvia; Liehr, Thomas; Rebordinos, Laureana (Frontiers in Genetics, 2019)
Global aquaculture production continues to increase rapidly. One of the most important species of marine fish currently cultivated in Southern Europe is Solea senegalensis, reaching more than 300 Tn in 2017. In the present work, up to 14 Bacterial Artificial Chromosomes (BAC) clones, which contain candidate genes involved in the immune system (b2m, il10, tlr3, tap1, tnfα, tlr8, trim25, lysg, irf5, hmgb2, calr, trim16 and mx), were analyzed and compared with other species, using techniques as multiple Fluorescence in situ Hybridization (mFISH), massive sequencing and bioinformatic analysis to know the genomic surrounding and syntenic chromosomal of the genomic region contained in each BAC clone. The mFISH showed that the group of genes hmgb2-trim25-irf5-b2m; tlr3-lysg; tnfα-tap1 and il10-mx-trim16 were co-localized in the same chromosomes. Synteny studies showed that the BACs studied were found in a smaller number of chromosomes than in the rest of the species analyzed; and from the phylogenetic studies, the evolutionary rate of immune system genes studied was similar among the species analyzed, given that, in the phylogenetic tree, the defined clusters observed were in accordance with the evolution of these species. This study contributes for a better understanding of the immune system structure and function of the Senegalese sole, which is essential for the development of new technologies and products to improve health and productivity.